Knowledge, Utilization, and Associated Factors of Nonpneumatic Antishock Garments for Management of Postpartum Hemorrhage among Maternity Ward Health Care Professionals in South Wollo Zone Health Facilities, Ethiopia, 2021: A Cross-Sectional Study Design - Wondimnew Gashaw Kettema; Zenebe Tefera Ayele; Mandefro Assefaw Geremew; Kibir Temesgen Assefa; Sindu Ayalew Yimer; Atrsaw Dessie Liyew; Besfat Berihun Erega; Eyaya Habtie Dagnaw (Obstetrics and Gynecology International)
Background. In 2017, approximately, 810 women died every day from preventable causes related to pregnancy and childbirth around the world. Obstetric hemorrhage, specifically postpartum hemorrhage, is the leading cause of preventable maternal mortality in the world. New strategies and technologies are needed to reduce the global public health epidemic of maternal mortality. However, nonpneumatic antishock garments were recently introduced and incorporated into teaching curriculums as a management modality for postpartum hemorrhage in Ethiopia. Therefore, this study assessed the knowledge, utilization and associated factors of nonpneumatic antishock garment among maternity ward healthcare professionals in the selected South Wollo zone health facilities, North West Ethiopia. Methods. An institutional-based cross-sectional study design was conducted from February 1 to April 30, 2021. A consecutive sampling technique was employed to collect the data. A self-administered semistructured English version questionnaire was used to collect the data. EPI-Info and SPSS were used for data entry and analysis, respectively. Bivariable and multivariable logistic regression analyses were used to analyze the association of nonpneumatic antishock garment utilization with independent variables. Results. A total of 244 maternity ward health care professionals participated. One hundred forty-six (59.8%) had a good knowledge of nonpneumatic antishock garments. About 110 (45.1%) of the participants have ever used it for the management of postpartum hemorrhage. Those having one nonpneumatic antishock garment (AOR = 2.7, 95% CI: 1.3, 5.5), two or more nonpneumatic antishock garments (AOR = 14.1, 5.7, 35.0), good knowledge (AOR = 5.2, 2.5, 10.7), and positive attitude (AOR = 2.5, 1.1, 5.7) and those who were receiving training (AOR = 2.2, 1.1, 4.4) at 95% CI were significantly associated with utilization of nonpneumatic antishock garments. Conclusion. The knowledge and utilization of nonpneumatic antishock garments for the management of postpartum hemorrhage were low. Those having more nonpneumatic antishock garments, good knowledge, and a positive attitude and those who received training were found to be significantly associated with nonpneumatic antishock garment utilization. The provision of training and availability of nonpneumatic antishock garments are the key actions to be taken to increase the utilization of nonpneumatic antishock garments.